The Effect Of Endurance Exercise On The Body's Defenses To Prevent Transmission Of The Covid Virus 19 For Student Penjaskesrek Undana - Veramyta Maria Martha Flora Babang; Maria Andriani Barek Ladjar; Ronald Dwi Ardian Fufu (UNIB Press, 2021)
Starting from the spread of viruses Covid 19 that swept across the world in particular in Indonesia, bringing the idea to create research that contribute in dealing with viruses Covid 19. This study aims to determine the effect of endurance exercise on the body's defenses to prevent transmission of the virus covid 19 for student penjaskesrek Undana. This research is an experimental study of Quasi-Experimental Designs by using Nonequivalent Comparison Group Design which compares the effect of endurance training on the two levels of physical fitness categories of Penjaskesrek students, those who have very Low and Low categories.Samples were 12 female students from Penjaskesrek Undana in semester 2, 4 and 6, where 6 people were in the less physical fitness category, and 6 in the physical fitness category were very Low.The findings of this study include; 1) In the group of physical fitness Low are Effect of Exercise Endurance Resilience Body face Virus Covid 19 on the students Penjaskesrek Undana significantly, 2) In the group of physical fitness is very Low are Effect of Exercise Endurance Resilience Body face Virus Covid 19 on the students Penjaskesrek Undana significantly.So, the conclusion is that endurance exercises are more effective in increasing endurance to deal with the Covid 19 virus.